2020
DOI: 10.1038/s41586-019-1817-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tuberculosis in macaques after intravenous BCG immunization

Abstract: Experimental design and safety The central aim of this study was to assess how the route and dose of BCG vaccination influence systemic and tissue-resident T cell immunity, and protection after Mtb challenge. Rhesus macaques were vaccinated with 5 × 10 7 colony-forming units (CFUs) of BCG by intradermal (ID high), AE or IV routes, or with a combination of both AE (5 × 10 7 CFUs) and ID

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
565
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(617 citation statements)
references
References 58 publications
48
565
2
2
Order By: Relevance
“…Previous studies in NHPs assessed antigen-specific immune responses in BAL at early time points macaques in infected macaques (35, 40-42), or during vaccination (43-45) (28). However, in-depth analysis of the phenotypes, functionality and kinetics of Mtb antigen-specific immune responses in blood and BAL during establishment and maintenance of asymptomatic latent infection have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in NHPs assessed antigen-specific immune responses in BAL at early time points macaques in infected macaques (35, 40-42), or during vaccination (43-45) (28). However, in-depth analysis of the phenotypes, functionality and kinetics of Mtb antigen-specific immune responses in blood and BAL during establishment and maintenance of asymptomatic latent infection have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, mice were immunized with BCG by intravenous injection, which has been shown to elicit stronger immune responses than other routine immunization routes (Darrah et al, 2020). DTH responses in vivo along with various immune factors were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Nine out of 10 macaques were highly protected against tuberculosis after intravenous administration of the BCG vaccine. 7 Animals immunized intradermally or by aerosols showed significantly higher rates of infection when challenged with Mycobacterium tuberculosis delivered intrapulmonary six months post-vaccination. Furthermore, intravenous delivery increased the count and persistence of antigen-responsive CD4 + and CD8 + T cells in the lungs.…”
Section: Intravenous Administration Of the Bcg Vaccine Improves Protementioning
confidence: 95%